The Influence of Father and Mother's Joint Decision Making on Children's Basic Immunization:Empirical Research on Indonesia's Demographic and Health Survey 2017 - Jondan Indhy Prastyo (Pusbindiklatren Bappenas, 2021)
The 2017 diphtheria outbreaks in Indonesia shows the downside of inadequate immunization for certain group that could endanger public health. Despite years of government intervention on this vaccine-preventable disease, insofar mandating basic vaccination for children from an early age, ultimately, it is parents that will decide on having their children being immunized. Utilizing the 2017 Indonesia Demographic and Health Survey, this study aims to uncover the association between parents' decision-making processes and their demographic variables to their children's immunization completion status. Logistic regression suggests discussion between parents in household's major purchases, more likely to result in complete basic immunization for their children. Additionally, mothers' traits, which are education, frequency of access to mass media, and exposure to medical professionals, are positively associated with compliance with basic vaccines administration. Differences in compliance can also be observed in children's gender and order of birth.